Loss of PDZK1 expression activates PI3K/AKT signaling via PTEN phosphorylation in gastric cancer. (1st July 2019) - Zhao, Chunjuan; Tao, Tao; Yang, Longyan; Qin, Qiong; Wang, Ying; Liu, Hua; Song, Ran; Yang, Xiaomei; Wang, Qiqi; Gu, Siyu; Xiong, Ying; Zhao, Dong; et al.
Abstract: Phosphorylation of PTEN plays an important role in carcinogenesis and progression of gastric cancer. However, the underlying mechanism of PTEN phosphorylation regulation remains largely elusive. In the present study, PDZK1 was identified as a novel binding protein of PTEN by association of PTEN through its carboxyl terminus and PDZ domains of PDZK1. By direct interaction with PTEN, PDZK1 inhibited the phosphorylation of PTEN at S380/T382/T383 cluster and further enhanced the capacity of PTEN to suppress PI3K/AKT activation. PDZK1 suppressed gastric cancer cell proliferation by diminishing PI3K/AKT activation via inhibition of PTEN phosphorylation in vitro and in vivo . The expression of PDZK1 was frequently downregulated in gastric cancer specimens and correlated with progression and poor prognosis of gastric cancer patients. Downregulation of PDZK1 was associated with PTEN inactivation, AKT signaling and cell proliferation activation in clinical specimens. Thus, low levels of PDZK1 in gastric cancer specimens lead to increase proliferation of gastric cancer cells via phosphorylation of PTEN at the S380/T382/T383 cluster and constitutively activation of PI3K/AKT signaling, which results in poor prognosis of gastric cancer patients. Highlights: PDZK1 inhibited the phosphorylation of PTEN at S380/T382/T383 cluster by directly interact with PTEN. PDZK1 suppressed gastric cancer cell proliferation by diminishing PI3K/AKT activation via inhibition of PTEN phosphorylation. The expression of PDZK1 was downregulated in GC specimens and correlated with progression and poor prognosis of GC patients.